Elite cross-country skiers develop greater physiological adaptations than biathletes in summer macrocycle - Feofilaktov, V. V.; Heil, D.; Myakinchenko, E. B.; Smith, D. M.; Kruchkov, A. S. (The Journal of Strength and Conditioning Research, 2025)
The study aimed to compare changes in aerobic, anaerobic, body composition, and training load parameters during a 6-month macrocycle in elite cross-country skiers (XC) and biathletes (BI). Twenty-six physiological and 8 training load parameters were analyzed retrospectively every month throughout a 6-month summer macrocycle for 32 elite male XC and 41 BI during 7 consecutive years. During the macrocycle, XC demonstrated lower body fat (6.7 ± 1.7 vs. 7.5 ± 1.5 kg, p < 0.001) and higher muscle mass (39.7 ± 3.0 vs. 38.5 ± 3.6 kg, p < 0.001) compared with BI. In addition, XC exhibited superior aerobic capacities at ventilatory threshold (VT), including oxygen pulse, oxygen uptake, power output, stroke volume, maximum oxygen uptake (Vo2max), and cardiac output, and maximum rate and power output for 10-second Wingate double poling (all p < 0.001). Both XC and BI showed simultaneous improvements in aerobic and anaerobic capacities, peaking during the competition period. The most consistent improvements observed throughout the macrocycle were in the upper-body power output at VT and Vo2max (correlation with the number of training days r = 0.3-0.4, p < 0.05). Cross-country skiers engaged in significantly higher volumes of low-intensity training (LIT), total strength training, and sport-specific training (SST) compared with BI (all p < 0.001). Conversely, BI had higher volume of high-intensity interval training (HIIT) in the final 4 months of the macrocycle. In conclusion, differences in training volumes (LIT, SST, and total strength) likely contributed to superior adaptations observed in XC. The study found that physiological adaptations were delayed rather than concurrent throughout the macrocycle.